Geochemical Variations of Basalts Erupted along the Reykjanes Ridge - Dobey, Zachary (The Ohio State University, 2015)
The Reykjanes Ridge is the section of the Mid-Atlantic Ridge just south of Iceland, and is the seaward extension of the Reykjanes Peninsula on Iceland. Reykjanes, meaning smoky peninsula, describes the steam from geothermal hot springs on the peninsula. This section of mid-ocean ridge shallows from the south, near the Charlie Gibbs Fracture Zone, towards Iceland, and this effect is ascribed to the presence of a mantle plume beneath Iceland. It is unknown whether the plume represents a compositional anomaly, a thermal anomaly, or both. Distinct variations in the geochemistry of basalt erupted along the Reykjanes Ridge towards Iceland have been described by previous workers (e.g., Schilling, 1973; Jones et al., 2014) and may reflect the presence of the plume beneath Iceland, but could also reflect interaction of magma with thickened Icelandic crust. Publication of a new compilation of geochemical data for mid-ocean ridge basalts by Gale et al. (2013) allows geochemical variations along the ridge to be re-examined using whole-rock data that have been filtered to exclude analyses of poor quality and that have been corrected for interlaboratory bias. The data used for this research are analyses of samples from 57°N to 64°N taken from this compilation of Mid-Ocean Ridge Basalt (MORB) analyses by Gale et al. (2013). The database includes major oxide data, trace element data and isotope data for 302 samples along with the latitude, longitude and depth at which the samples were collected. These analyses are plotted on variation diagrams to assess the role of crystallization and of other processes in controlling the composition of basalts erupted along the ridge. The analyses are also plotted against latitude in order to establish changes in magma geochemistry over the length of the ridge. Significant variations in major oxide and trace element composition occur as the ridge approaches Iceland, with a distinct change in composition occurring at 60.5°N. In order to further understand how specific groups of elements changed over the length of the ridge, the data was normalized to the average composition of normal mid-ocean ridge basalt, primitive mantle, and CI chondrite (for rare earth elements only). The results from this research shows that variations in major oxides are consistent with control by crystallization, and there is remarkable similarity between whole rock and volcanic glass analyses. Trace element data show considerable variations in samples collected along the ridge, but do not provide convincing evidence for variation with assimilation of thickened crust.It is concluded that the mantle plume reflects a compositional anomaly, but it is not clear that there is also a thermal anomaly. Funded by: Shell Exploration and Production Co. No embargo